New didactic tools for musical learning: The production system and goal stacking - Alonso Jartín, Ruth; Posse Robles, Damián Saúl (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The aim of this research is to weigh, through documentary review, one of the fundamental aspects of musical learning: the achievement of self-regulated learning by students. To this end, the review of the Production System theory (Anderson, 1981 and 1982) is proposed, which will guide the skills acquisition process, the function of Goal Stacking, which will order the process, Motivation, as an amplifier of talent and the Metacognitive and Affective model of Efklides (2011), as an effective procedure for the acquisition of the main objective of this study.